Perspectives to the Relations between the Estonian Folklore Archives and the Folklore Archives of the Finnish Literature Society - Irma-Riitta Järvinen (Journal of Ethnology and Folkloristics)
The origin of the relations between Finnish and Estonian folklorists goes far back to the days of Elias Lönnrot and Friedrich Reinhold Kreutzwald in the first half of the 19th century. In this article, however, I shall concentrate on those decades since the 1930s, when the two archives, the Estonian Folklore Archives and the Folklore Archives of the Finnish Literature Society have existed as institutions. I shall highlight some events, joint projects, historical turning points, and pay attention to individuals, who have had more influence on developing these relations. There were periods of time when the contacts were not possible between the institutions, but still, the continuity of relations existed between individuals. My point of view is micro-historical, as the study of micro-history is interested on the small scale level on the individual, in opposition to macro-history that concentrates on the great changes brought along by political events, on the history of “great men and women”, as well as on the history of institutions. In the history of the folklore archives in Finland and Estonia, we can recognise both of those levels and pay attention to the way how they are intertwined.